Fractured intubating stylet: A case of airway foreign body in Intensive care Unit - Shrestha, Babu Raja; Baral, Bikash; Binod, Gautam (Bangladesh Critical Care Journal, 2021)
Abstract not available Bangladesh Crit Care J March 2021; 9(1): 41-42